Portable negative‐pressure wound therapy for pyoderma gangrenosum: Report of two cases. Issue 4 (13th December 2017) - Yamaguchi, Yasuyuki; Yanagi, Teruki; Sato, Kazumasa; Yoshimoto, Norihiro; Hirata, Yu; Ujiie, Inkin; Nishimura, Machiko; Natsuga, Ken; Shiiya, Chihiro; Tsukinaga, Ichiro; Shimizu, Hiroshi
Abstract: Pyoderma gangrenosum is a chronic non‐infectious neutrophilic dermatosis that causes undermining ulcers. Topical therapies for the deep ulcers of pyoderma gangrenosum have not been established. To investigate whether negative‐pressure wound therapy is effective for a pyoderma gangrenosum ulcer, we used the PICO single use negative‐pressure wound therapy system (Smith & Nephew, London, UK) for two pyoderma gangrenosum patients. In these cases, the ulcers decreased in size and necrolytic tissue was removed notably. Moreover, there were no secondary infections nor was there Koebner phenomena. Our cases suggest that portable negative‐pressure wound therapy can be a treatment option for deep, intractable ulcers caused by pyoderma gangrenosum. Because portable negative‐pressure wound therapy devices afford increased mobility to patients, they can give the patient a better quality of life than standard negative‐pressure wound therapy systems do.